Salmonella spvC Gene Inhibits Pyroptosis and Intestinal Inflammation to Aggravate Systemic Infection in Mice - Zuo, Lingli; Zhou, Liting; Wu, Chaoyi; Wang, Yanlin; Li, Yuanyuan; Huang, Rui; Wu, Shuyan (Frontiers in Microbiology, 2020)
Salmonella enterica serovar Typhimurium (S. Typhimurium) is a primary foodborne pathogen infecting both humans and animals. Salmonella plasmid virulence C (spvC) gene is closely related to S. Typhimurium dissemination in mice while the mechanisms remain to be fully elucidated. Pyroptosis, a gasdermin-mediated inflammatory cell death, plays a role in host defense against bacterial infection. Whereas the effect of spvC on pyroptosis and its function in inﬂammatory injury induced by S. Typhimurium is rather limited. In our study, C57BL/6 mice and J774A.1 cells infected with S. Typhimurium wild type strain SL1344, spvC deletion mutant, spvC K136A site-directed mutant and complemented strain were used to investigate potential pathogenesis of spvC. We verity that SpvC attenuates intestinal inflammation, suppresses pyroptosis through phosphothreonine lyase activity and reduces pyroptosis in caeca. Moreover the reduction of inflammation via spvC results in systemic infection. These findings demonstrate spvC inhibits pyroptosis and intestinal inflammation to promote bacterial dissemination, which provide new strategies for controlling systemic infection caused by Salmonella and novel insights for the treatment of other corresponding diseases.